Molten Salts–Assisted Fabrication of Fe, S, and N Co‐Doped Carbon as Efficient Oxygen Reduction Reaction Catalyst. Issue 1 (26th September 2019) - Lv, Mengyao; Fan, Fenghui; Pan, Longhai; Shen, Hangjia; Pervaiz, Erum; Wang, Jiacheng; Yang, Minghui; Wang, Jun
Abstract : Fabrication of an oxygen reduction reaction (ORR) catalyst is the key to an efficient and fast electrocatalytic process in a fuel cell for energy conversion. A reasonable strategy for the synthesis of electrocatalysts is one of the most promising ways for developing precious metal‐free ORR catalysts. Herein, the synthesis of a highly active Fe3 O4 ‐based catalyst using a facile molten salts method is proposed. The electrocatalytic analysis shows superior ORR performance with an admirable half‐wave potential ( E 1/2 = 0.83 V), comparable with the commercial 20 wt% Pt/C. In contrast, primary Zn–air battery, using synthesized Fe, S–N–C as an air‐cathode, displays an open‐circuit potential of 1.44 V and a high power density of 84.3 mW cm −2 . Abstract : An Fe3 O4 ‐based porous carbon material is synthesized via a molten salts method and shows Pt/C comparable activity toward oxygen electroreduction in alkaline media.